STRUKTUR CERITA RAKYAT LEGENDA SI BAJAK SI KELAK KULIT DAN FUNGSI SOSIALNYA PADA MASYARAKAT DESA SIMALEGI KECAMATAN SIBERUT BARAT KABUPATEN KEPULAUAN MENTAWAI - Ramadhani, Rahimi; WS, Hasanuddin; Juita, Novia (Jurnal Bahasa dan Sastra, 2017)
This research is aimed to describe: (1) the structure of folklore legends Si Bajak Si Kelak Kulit in Simalegi Village, West Siberut, District Mentawai Islands; (2) the social function of folklore legends Si Bajak Si Kelak Kulit in Simalegi Village, West District of Siberut, Mentawai Islands. This sort of research is a qualitative study using descriptive methods. This research data is folklore legends Si Bajak Si Kelak Kulit in Simalegi Village, West District of Siberut, Mentawai Islands. These data was collected from informants through interview, observation, and interviews records by informants. The data were analyzed by the steps of: (1) a data inventory phase; (2) classification of data; (3) the stage of discussion or conclusion from data classification results; and (4) the stage of reporting. Based on the research, was found the following statements. (1) the structure of folklore legends Si Bajak Si Kelak Kulit in Simalegi Village, West District of Siberut, Mentawai Islands including: (a) a language style, (b) the viewpoint of the speaker (the informant), (c) character and characterization, (d) the storyline/plots of the folklore, (e) the background, (f) the theme, and (g) the moral of folklore; (2) social functions contained in folklore is to educate, entertain, also to strengthen the tradition, as the way to bequeath the tradition.Keywords: structure, social function, folklores